Electroacupuncture Alleviates Diabetic Peripheral Neuropathy by Regulating Glycolipid-Related GLO/AGEs/RAGE Axis - Wang, Xuan; Li, Qian; Han, Xu; Gong, Meirong; Yu, Zhi; Xu, Bin (Frontiers in Endocrinology, 2021)
Diabetic peripheral neuropathy(DPN) is one of the most common complications of diabetes mellitus(DM) and perplex over one-third of all patients. Neuropathic pain and nerve dysfunction induced by DM is related to the increase of advanced glycation end products(AGEs) produced by reactive dicarbonyl compounds in a hyperglycemia environment. AGEs induce the expression of pro-inflammatory cytokines via the main receptor(RAGE), which has been documented to play a crucial role in the pathogenesis of diabetic peripheral neuropathy. Electroacupuncture(EA) has been reported to have a positive effect on paralgesia caused by various diseases, but the mechanism is unclear. In this study, we used high-fat-fed low-dose streptozotocin-induced rats as a model of type 2 diabetes(T2DM). Persistent metabolic disorder led to mechanical and thermal hyperalgesia, as well as intraepidermal nerve fiber density reduction and nerve demyelination. EA improved neurological hyperalgesia, decreased the pro-inflammatory cytokines, reduced the generation of AGEs and RAGE, and regulated the glyoxalase system in the EA group. Taken together, our study suggested that EA plays a role in the treatment of T2DM-induced DPN, and is probably related to the regulation of metabolism and the secondary influence on GLO/AGE/RAGE axis.